(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2020)
Background : Gastroenterological malignancies represent one of the greatest public health issues worldwide leading to significant numbers of global death. This study was performed to evaluate survival trend that is still alive in patient with GI malignancies from diagnosis to post treatment era with both definitive and palliative care. Materials and methods: This observational prospective study done at BSMMU and different hospitals in Dhaka city admitted patient with gastrointestinal malignancies during the period of 20th October 2008 to 30th April 2010 getting definitive and palliative treatment. The data were analyzed by simple frequency distribution table. Results: The most common cancers were carcinoma stomach, hepatocellular carcinoma and colonic carcinoma among total 350diagnosed cancer patients and were followed up for mean period 6.7 months (±5.5). Among them 138 (39.4%) patients were alive and 212 (60.6%) were expired during study period. Patient’s receiving curative or palliative treatment, 38.5% survived for less than 3 months, 23.1 % for 4 to 6 months, 12.6 % for 7 to 9 months, 3% for 10 to 12 months, 14.6% for 14 to 24 months and only 5.1% for more than 24 months. Only 18% (63) patients received curative treatment whereas 82% (287) patients palliative treatment. Out of 63 patients, 31.7% (20), 22.2% (14) and 9.5% (6) patients received curative treatment survived more than 24 months, 13-20 months and 10-12 months respectively whereas only 6.3% (4) patients survived only 3 months. Out of 287 patients, 45.6% (131), 73% (25.4), 11.5% (33) and 10.8% (31) patients received palliative treatment survived less than 3 months, 4-6 months, 7-9 months and 13-24 months respectively whereas only 4.1%% (4) patients survived only 24 months. Conclusion: We observed to estimate the survival trend and the impact of available treatment modalities as well as to determine the outcome for different gastrointestinal malignancies in Bangladesh. JCMCTA 2019 ; 30 (2) : 41-46